A map of long-term care for people with dementia at the level of local communities - Mali, Jana (Metodološki zvezki, 2023)
Long-term care for people with dementia has been studied using the Rapid Assessment of Needs and Services method, which has been used to map long-term care needs in order to stimulate the development of care that effectively meets the needs of people with dementia. In this paper, we present the results of three focus groups with key stakeholders in long-term care for people with dementia in three selected communities, involving 29 people from a variety of organisations: social work centres, homes for the older people, health centres, general and psychiatric hospitals, municipalities and non-governmental organizations. Qualitative analysis of the empirical material showed that the following problems are prevalent in the communities: (i) acute and unmet needs of informal caregivers, (ii) a multi-tiered system of long-term care that puts people in an unequal position, (iii) a lack of community-based long-term care, and inadequate responses to the needs of people with dementia. Even in communities where there are various forms of support, both institutional and community-based, available across all service sectors, long-term care for people with dementia is based on informal care. We propose the development of a national strategy for family caregivers, with special attention to informal caregivers of people with dementia. The support offered by existing facilities is inadequate, poorly accessible, or nonexistent. Homes for older people are overcrowded, and people with dementia wait months or years to be admitted to a home. Home-based assistance is not evenly distributed across communities, and its scale (20 hours per week) in particular is insufficient to meet the needs of people with dementia. There is a lack of alternative forms of care that enable people with dementia to remain in their own home environment for as long as possible, for example in the form of personal assistance. We suggest that the development of long-term care for people with dementia should be based on the proposed research methodology.
Keywords: community care; demenca; dementia; dolgotrajna oskrba; elderly; lokalna skupnost; long-term care; potrebe; rapid assessment of needs and services; social work; socialno delo